CLASSROOM ASSESSMENT FOR DESCRIPTIVE PARAGRAPH WRITING: A STUDY ON TENTH-GRADE VOCATIONAL STUDENTS - Didik Rinan Sumekto (English Review: Journal of English Education, 2026)
Classroom assessment enormously represents a teacher-feedback designed that collects on-going evidence of students’ learning experience and achievement. This study examined the effectiveness of classroom assessment with teacher feedback in promoting descriptive paragraph writing among tenth-grade vocational high school students in Yogyakarta, Indonesia. Twenty-four students (n = 24) completed two descriptive paragraph writing tasks on family background themes over two sessions. Data were analyzed using descriptive statistics, paired t-tests, chi-square goodness-of-fit tests, and principal components analysis (PCA) for learning attitudes (honesty, collaboration, respectfulness, communication, social relationships). Results showed mean scores of 65.63 (SD = 6.63) for the first test and 68.17 (SD = 8.50) for the second test; neither met the teacher's minimum passing grade of 72.00. The difference between tests was not statistically significant. The PCA revealed a Kaiser-Meyer-Olkin value of .269, indicating poor factorability of learning attitude items. Bartlett's test of sphericity was significant (χ² = 23.249, df = 3, p = .046). The study concludes that while teacher feedback contributed to modest writing improvement, whilst the learning attitudes did not demonstrate coherent factorial structure since the small sample size (n = 24) is below PCA’s minimal recommendation and single-site design also limits generalizability.